Determining future water demand needs for domestic users in Pahang - Norliyana, Sazali (2017)
Water demand is to determine the water supply capacity needed for a particular population. As population is constantly growing, the domestic water demand also increasing. To fulfil the water demands needs, the projected water demand planning have been developed by local authorities. However, there is still have insufficient water supply occur in the some areas. The main objective of this study is to determine future water demand needs for domestic users in Pahang. To achieve the main objective of study, the specific study were performed as follow; develop forecast population growth and compare domestic water demands trends and water supply by district level in Pahang. The statistical analysis of population data and domestic water demands will be made based on the research. Therefore, the several methods will be applied to get information in order to achieve the objectives of study. For this study, the method of data collecting are based on researched from various state report from government agencies, journals, articles and website. An analysis data are developed to forecast population growth and water demand by equation of study. All data analysis were tabulate and presented in graphical chart. The period of study was conducted in 10-years interval from 2020 to 2050. The result of the study shows the forecast population is growing constantly, the domestic water demand will be increased. The comparison between domestic water demand and water supply have been analysed to identify the problem that will occur in the future. In conclusion, the research objective of this study are achieved when the forecast of population growth and domestic water demand trends have developed by district level in Pahang. If the water supply does not meet the demand caused by population growth, this might be a problem for domestic users someday.